SpHincterotomy for Acute Recurrent Pancreatitis Randomized Trial: Rationale, Methodology, and Potential Implications. Issue 8 (September 2019) - Coté, Gregory A.; Durkalski-Mauldin, Valerie L.; Serrano, Jose; Klintworth, Erin; Williams, April W.; Cruz-Monserrate, Zobeida; Arain, Mustafa; Buxbaum, James L.; Conwell, Darwin L.; Fogel, Evan L.; Freeman, Martin L.; Gardner, Timothy B.; et al.
Abstract : Objectives: In patients with acute recurrent pancreatitis (ARP), pancreas divisum, and no other etiologic factors, endoscopic retrograde cholangiopancreatography (ERCP) with minor papilla endoscopic sphincterotomy (miES) is often performed to enlarge the minor papillary orifice, based on limited data. The aims of this study are to describe the rationale and methodology of a sham-controlled clinical trial designed to test the hypothesis that miES reduces the risk of acute pancreatitis. Methods: The SpHincterotomy for Acute Recurrent Pancreatitis (SHARP) trial is a multicenter, international, sham-controlled, randomized trial comparing endoscopic ultrasound + ERCP with miES versus endoscopic ultrasound + sham for the management of ARP. A total of 234 consented patients having 2 or more discrete episodes of acute pancreatitis, pancreas divisum confirmed by magnetic resonance cholangiopancreatography, and no other clear etiology for acute pancreatitis will be randomized. Both cohorts will be followed for a minimum of 6 months and a maximum of 48 months. Results: The trial is powered to detect a 33% risk reduction of acute pancreatitis frequency. Conclusions: The SHARP trial will determine whether ERCP with miES benefits patients with idiopathic ARP and pancreas divisum. Trial planning has informed the importance of blinded outcome assessors and long-term follow-up.